Effect on Movement and Balance Function with Robot Training for Stroke Patients in Lower Limb Rehabilitation - Zhiyuan WU; Kunbin LI; Shuwei LOU; Xianli YAO; Pingge SUN; Xiaoxing LI (康复学报)
Objective:To observe the effect of lower limb rehabilitation robot training on movement and balance function of stroke patients.Methods:A total of 123 patients with stroke treated in affiliated Zhengzhou central hospital of Zhengzhou university were randomly divided into the control group and observation group according to the order of admission time, with 60 cases and 63 cases respectively. There are three cases of the observation group fell off or suspended for various reasons during the treatment. The control group received routine rehabilitation training,30 min per day, once a day, five days a week, continuous treatment for eight weeks. The observation group received lower limb rehabilitation robot training based on the control group, and the standing angle, step mode, left/right leg movement range were choosed according to the patient's physical condition, set the walking frequency about 20 to 30 steps per minute, the training frequency was 30 min per day, once a day, five days a week, continuous treatment for eight weeks. The step speed, step frequency, the amplitude difference of left and right step, BBS score, FMA score, NIHSS score were recorded in the two groups after treatment.Results:Before treatment, there was no significant difference in the step speed, step frequency, left and right step amplitude difference, BBS score, FMA score, NIHSS score of both groups (P>0.05). Compared with before treatment, the walking speed and frequency of both groups after eight weeks'treatment were higher, the amplitude difference of left and right step in both groups after treatment for eight weeks was lower, the walking speed and frequency of observation groups were higher than those of the control group, the left and right step amplitude difference of observation groups were lower than those of the control group, with statistically significant differences (P<0.05). Compared with before treatment, BBS score and FMA score of both groups were significantly increased and NIHSS score was significantly reduced after treatment for four and eight weeks. BBS score and FMA score of the observation group were significantly higher than those of the control group at the same time after treatment, and NIHSS score was significantly lower than that of the control group, with statistically significant differences (P<0.05).Conclusion:The application of lower limb rehabilitation robot training can reduce the neurological deficit in stroke patients, and promote the recovery of balance function and lower extremity motor function.